Ответы и объяснения

pechenkalol
MashaKlimova

 

87*43 + \frac{87^3 - 43^3}{44} = 87*43 + \frac{(87 - 43)(87^2 + 87*43 + 43^2)}{44} =\\\\\ 87*43 + \frac{44* (87^2 + 87*43 + 43^2)}{44} = 87*43 + 87^2 + 87*43 + 43^2 =\\\\ 87^2 + 2*87*43 + 43^2 = (87+43)^2 = 130^2 = \boxed{ 16900 } \\\\\\ a^3 - b^3 = (a - b)(a^2 + ab + b^2)\\\\ a^2 + 2ab + b^2 = (a + b)^2

 

5.0
1 оценка
1 оценка
Оцени!
Оцени!
MashaKlimova

87*43+(87^3-43^3)/44=

=87*43+((87-43)(87^2+87*43+43^2))/44=

=87*43+(44(87^2+87*43+43^2))/44=

=87*43+87^2+87*43+43^2=

=87^2+2*87*43*43^2=(87+43)^2=130^2=16900

0.0
0 оценок
0 оценок
Оцени!
Оцени!